2007
DOI: 10.1021/jp0672656
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Reactions of Gaseous HNO3 and NO2 on the Clay Minerals Kaolinite and Pyrophyllite

Abstract: Airborne clay mineral particles have long atmospheric lifetimes due to their relatively small size. To assess their impact on trace atmospheric gases, we investigated heterogeneous reactions on prototype clay minerals. Diffuse reflectance infrared spectroscopy identified surface-adsorbed products formed from the uptake of gaseous nitric acid and nitrogen dioxide on kaolinite and pyrophyllite. For kaolinite, a 1:1 phyllosilicate, HNO3 molecularly adsorbed onto the octahedral aluminum hydroxide and tetrahedral s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
69
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(79 citation statements)
references
References 35 publications
6
69
1
3
Order By: Relevance
“…S3 (ESI †), a Langmuir adsorption isotherm for water vapor and the Langmuir-Hinshelwood reaction mechanism for NO 2 on these particles can adequately describe the influence of RH on the uptake coefficient. 6 and from 7 Â 10 À7 to 7.7 Â 10 À6 for NO 2 on hematite under dry conditions, 5,19 respectively. At high RH (32-74%), the average g t (10 s) of NO 2 on kaolin was (4.42 AE 1.17) Â 10 À8 , and it was (2.83 AE 0.84) Â 10 À7 on hematite.…”
Section: Experimental Methodsmentioning
confidence: 98%
See 4 more Smart Citations
“…S3 (ESI †), a Langmuir adsorption isotherm for water vapor and the Langmuir-Hinshelwood reaction mechanism for NO 2 on these particles can adequately describe the influence of RH on the uptake coefficient. 6 and from 7 Â 10 À7 to 7.7 Â 10 À6 for NO 2 on hematite under dry conditions, 5,19 respectively. At high RH (32-74%), the average g t (10 s) of NO 2 on kaolin was (4.42 AE 1.17) Â 10 À8 , and it was (2.83 AE 0.84) Â 10 À7 on hematite.…”
Section: Experimental Methodsmentioning
confidence: 98%
“…The decline of the initial g with RH can be ascribed to competitive adsorption between H 2 O and NO 2 , similar to the competitive adsorption of O 3 , NO 2 or COS with H 2 O on mineral oxides. 22,24,25 It has been found that a monolayer of H 2 O on kaolin is achieved at 13% RH, 6 and at 10% RH on hematite. 24 The initial g of H 2 O on mineral dust (4.2 AE 0.7 Â 10 À2 ) 42 is much larger than that of NO 2 , as discussed above.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 3 more Smart Citations